Feasibility assessment of grid-tied rooftop solar photovoltaic systems for industrial sector application in Uganda. (April 2019) - Mukisa, Nicholas; Zamora, Ramon; Lie, Tek Tjing
Highlights: An alternative approach for determining rooftop area suitable for solar PV deployment using validated open source tools and a mathematical algorithm is proposed. Possible solar PV generation and energy supply to the industry's demand were evaluated. An economic feasibility of the proposed solar PV system was evaluated. Annual energy cost analysis due to implementation of solar PV system by the industry was evaluated. Abstract: This paper proposes an alternative approach to determination of rooftop area suitable for solar PV deployment by using validated open source tools that require minimal computational know-how. The paper goes ahead to evaluate the feasibility of implementing grid-tied rooftop solar PV systems in the industrial sector in Uganda. For the considered sample space of 36 industries, a total suitable rooftop area for solar PV application was found to be around 164594.56 m 2 and would be able to accommodate about 25.4 MWp capacity. The investigation of energy generation potential showed the possibility of annual energy yield in the range of 1046 kWh/kW–1344 kWh/kW for all roof orientations and roof tilt angles in the range 0°–45°. The economic analysis for PV system in Uganda resulted in an LCOE of 5.75 US cent/kWh, internal rate of return of 7% and BCR of 1.27 for a system implemented entirely on equity. The sensitivity to debt of economic analysis indicated that the project with short loan period of 5 years was still feasible when the loan share of investment cost reached up to 75%.